2001
DOI: 10.1152/ajpheart.2001.281.3.h1380
|View full text |Cite
|
Sign up to set email alerts
|

Shear level influences resistance artery remodeling: wall dimensions, cell density, and eNOS expression

Abstract: The magnitude of shear stimulus has been shown to determine the level of growth factor expression in cell culture. However, little is known regarding what effect shear level has on specific arterial wall remodeling events in vivo. We have hypothesized that the rate of luminal diameter change and specific remodeling events within the arterial wall layers are dependent on shear level. Selective ligations were made to alter the number of microvascular perfusion units of mesenteric arteries within the same animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
194
0
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(227 citation statements)
references
References 57 publications
21
194
0
8
Order By: Relevance
“…30 Similar observations were made by our group and others. 27,30,41,42 In the present study, we observed flowinduced outward hypertrophic remodeling but no hypotrophy in resistance arteries exposed to low blood flow in normotensive Wistar rats studied between 10 and 14 weeks of age. This indicates dependence of flow-related arterial remodeling on rat age 43 and strain.…”
Section: Discussionsupporting
confidence: 56%
“…30 Similar observations were made by our group and others. 27,30,41,42 In the present study, we observed flowinduced outward hypertrophic remodeling but no hypotrophy in resistance arteries exposed to low blood flow in normotensive Wistar rats studied between 10 and 14 weeks of age. This indicates dependence of flow-related arterial remodeling on rat age 43 and strain.…”
Section: Discussionsupporting
confidence: 56%
“…22,23 Subsequent animal studies consolidated the link between increases in flow, wall shear stress, endothelial NO synthase expression, and NO bioactivity. 24,25 Together, this evidence strongly suggests that flow and shear are physiological stimuli that induce NO production from the endothelium in vivo. However, it is important to note that other vasoactive substances can also be released by the endothelium in response to shear stress (eg, prostacyclin and endothelial derived hyperpolarizing factor).…”
Section: Physiological Basis For the Prognostic Value Of Fmdmentioning
confidence: 86%
“…Because it is well known that shear stress is a potent physiologic stimulus for NO release, the increased levels of basal shear stress may lead to an upregulation of endothelial nitric oxide synthase (eNOS). A recent training study in patients with coronary artery disease 33 and previous in vivo 34 and cell culture studies 2,35 have shown that increases in shear stress levels are associated with an elevation of eNOS messenger ribonucleic acid protein and NOS activity. A second possible explanation may be the lack of periods of high shear stress in the vessels supplying the paralyzed and inactive leg muscles of people with SCI, which may contribute to an upregulation of NO responsiveness.…”
Section: Endothelial Functionmentioning
confidence: 97%